Indonesian Export Analysis: Autoregressive Distributed Lag (ARDL) Model Approach - Syarifah Labibah; Abd. Jamal; Taufiq C. Dawood (Journal of Economics, Business, and Accountancy Ventura, 2020)
There are some factors predicted tohave an effect on the countries’ economic devlopment. This study aimed to analyze the long-term and short-term effects of In-flation, Exchange Rate, and Foreign Economic Growth (the destination of the United States, China, and Japan) on the Indonesian Export. The Auto-Regressive Distributed Lag (ARDL) Model is used in this analysis from 1968 through 2017. The results of the analysis show that in the long-term, the inflation and the economic growth in China as well in Japan has a positive sign and significant effect on Indonesian exports. In addition, in the short-term, the US exchange rate and economic growth have a positive significant effect on Indonesian exports.